'Can't hack the whack': Exploring young men's gendered discourses on time in prison. (November 2021) - Murray, Conor
Although there is a growing body of literature that documents prisoners' experiences of time in custody, and while prison is usually the experience of young men, there are few studies that focus on young men's experiences of time in prison. Based on findings from a 9-month ethnographic study of a young offenders' institution, this article addresses these gaps in the literature, exploring how young men's (aged 18–24) gendered discourses on time in prison shape their prison experience. This is explored through three principal themes: 'heavy-whacking', the subordination of those young men who were struggling to cope with their time in prison; 'time-hierarchy', the gendered discourses in prison that associated sentence length with toughness; and the 'Young-Elders', a group of young men who benefitted from the gendered discourses in the prison and lived relatively free from stigmatisation on the most enhanced landings in the prison.